2010
DOI: 10.1002/joc.2131
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological impacts of land use/land cover change in a large river basin in central–northern Thailand

Abstract: ABSTRACT:The purpose of this study is to determine the hydrological impacts of land use/land cover (LULC) change in the Yom watershed in central-northern Thailand over a 15-year period using an integration of remote sensing, Geographic Information System, statistical methods, and hydrological modelling. The LULC changes showed an expansion of urban areas by 132% (from 210 km 2 in 1990 to 488 km 2 in 2006). The Yom River's daily discharge long-term trend significantly increased at most of the measurement statio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(31 citation statements)
references
References 16 publications
0
30
0
1
Order By: Relevance
“…Most of the studies examine regional impacts of land surface states on climate (Costa and Pires, 2010;Fall et al, 2010aFall et al, , 2010bGe, 2010;Kishtawal et al, 2010;Mishra et al, 2010;Moore et al, 2010;Petchprayoon et al, 2010;Sertel et al, 2010;Takahashi et al, 2010;Tokairin et al, 2010;Xiao et al, 2010). However, several studies take a global perspective of land-cover consequences Kvalevåg et al, 2010;Lawrence and Chase, 2010;Strengers et al, 2010).…”
Section: Impacts Of Land Use Change On Climatementioning
confidence: 99%
See 2 more Smart Citations
“…Most of the studies examine regional impacts of land surface states on climate (Costa and Pires, 2010;Fall et al, 2010aFall et al, , 2010bGe, 2010;Kishtawal et al, 2010;Mishra et al, 2010;Moore et al, 2010;Petchprayoon et al, 2010;Sertel et al, 2010;Takahashi et al, 2010;Tokairin et al, 2010;Xiao et al, 2010). However, several studies take a global perspective of land-cover consequences Kvalevåg et al, 2010;Lawrence and Chase, 2010;Strengers et al, 2010).…”
Section: Impacts Of Land Use Change On Climatementioning
confidence: 99%
“…The observational studies use in situ climate data (Petchprayoon et al, 2010;Xiao et al, 2010), satellite measurements (Ge, 2010;Kishtawal et al, 2010) and data from regional reanalyses (Fall et al, 2010a(Fall et al, , 2010b. The modelling studies use regional atmospheric models (Moore et al, 2010;Sertel et al, 2010;Takahashi et al, 2010;Tokairin et al, 2010;Xiao et al, 2010), global climate models Costa and Pires, 2010;Kvalevåg et al, 2010;Lawrence and Chase, 2010;Strengers et al, 2010) and one uses a land surface model run offline (Mishra et al, 2010).…”
Section: Impacts Of Land Use Change On Climatementioning
confidence: 99%
See 1 more Smart Citation
“…Petchprayoon et al (2010) studied the hydrological impact of land use/land cover change in the Yom River watershed, in northern Thailand. They showed that the expansion of urban areas by 132% (from 210 km 2 in 1990 to 488 km 2 in 2006) resulted in a positive temporal trend in river discharge.…”
Section: Introductionmentioning
confidence: 99%
“…Many methods have been developed for isolating the effect of land use change from climate variations on regional hydrology. These methods include the paired catchment approach (Brown et al, 2005;Zégre et al, 2010), statistical methods (Costa et al, 2003;Sun et al, 2006;Petchprayoon et al, 2010), and a hydrological model (Haverkamp et al, 2005;Mao and Cherkauer, 2009;Baker and Miller, 2013). Raymond et al (2008) suggested that land use change and management have been more important than climate variation to increase riverine water export from the Mississippi River over the past 50 years.…”
mentioning
confidence: 99%